PARÂMETROS DE ALFABETIZAÇÃO CIENTÍFICA NOS LIVROS DIDÁTICOS DE CIÊNCIAS: analisando a unidade botânica - NAVEGANTES, Ronan Santos dos (2024)
Throughout its construction, the science curriculum has undergone continuous transformations in an ideal of contemporary educational culture, aiming at transforming didactics in science education, whose final product is a critical individual capable of exercising his citizenship in the fullness of his rights. The way we turn students into critical people is through the education we do. Such changes are aimed at the teaching of botany which is often developed only with the use of textbooks. In this way, the present study aimed to verify the potential of science textbooks of the 7th grade of the fundamental for the promotion of scientific literacy focused on teaching botany. The study was qualitative and during the period of two weeks, from June 11 to 25, 2017, four copies of textbooks were acquired for data collection and analysis, all of the year 2015. The books are arranged in alphabetical order and identified as LD1, LD2, LD3 and LD4. The data were organized according to the Bardin content analysis that has techniques such as: composition of the corpus, floating reading, clipping coding, enumeration and aggregation and categorization. However, the categories of scientific literacy: practical, civic, cultural, economic or professional were defined from different articles. As a result, it was found that there was a great variability of these parameters in each analyzed specimen, mainly when comparing one work with the other. The category of AC Practice was the one that presented a high potential of being reached with the use of textbooks, the other categories appear in parts of the unit in a timid manner, but, in the process of being introduced in the books. In this way, we can conclude that the variability of the potentials present in the textbooks represented by the categories, can indicate a fragmented Scientific Literacy, that is, depending on the category of interest.